(3y+9)/6y

Simple and best practice solution for (3y+9)/6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3y+9)/6y equation:


y in (-oo:+oo)

y*((3*y+9)/6) = 0

(y*(3*y+9))/6 = 0

( 3*y+9 )

3*y+9 = 0 // - 9

3*y = -9 // : 3

y = -9/3

y = -3

( y )

y = 0

y in { -3, 0 }

See similar equations:

| b+1=0 | | -31/5=b+4/5 | | w-10=-6 | | 11/9=w+2/9 | | m+10=59/6 | | P1=C2+F2/160-P1 | | 49/4=d+1/4 | | d-1=-11 | | t/6=4/7 | | x^2+13+30= | | 1/2+x=9/2 | | 7/20=k-2/5 | | w-1/3=23/3 | | 1/5a=2 | | -9+x=-58/7 | | d+7=25/4 | | k/-6=-4 | | 8+d=15 | | m-2/3=22/3 | | 43/9=n+7/9 | | 1/18=b-5/6 | | 2/5t=-1/5 | | 2/5x=4 | | -20/3=b-7 | | -1/7k=-6/49 | | 0=w-2/9 | | 5k=-10 | | d+1=17/10 | | -23/55=w-3/5 | | 1/2+d=21/2 | | n+3=23/9 | | 17/10=x+2 |

Equations solver categories